Modeling and Optimizing Strategies for Strengthening PKBM Sustainability - Suyadi Suyadi; Bibin Rubini; Dian Wulandari (Journal La Edusci, 2026)
This study aimed to develop strategies for strengthening the sustainability of Community Learning Centers or PKBM by examining the direct and indirect effects of servant leadership, organizational climate, Organizational Citizenship Behavior, and the effectiveness of education and training. This study employed a quantitative correlational approach involving 165 heads and tutors from 39 PKBM units in East Bogor Regency. Data were collected through a structured questionnaire and analyzed using descriptive statistics, prerequisite tests, path analysis, and SITOREM analysis. The findings showed that servant leadership, organizational climate, Organizational Citizenship Behavior, and the effectiveness of education and training had positive direct effects on PKBM sustainability. Servant leadership and organizational climate also had indirect effects on PKBM sustainability through Organizational Citizenship Behavior and the effectiveness of education and training. The SITOREM analysis identified several indicators requiring priority improvement, including conceptualization, forward looking orientation, satisfaction with activities, meeting community needs, development and empowerment, availability of teaching staff, PKBM development, and work mechanisms. These findings indicate that PKBM sustainability is shaped not only by leadership and organizational conditions, but also by voluntary work behavior and continuous human resource development. The study recommends strengthening servant leadership, improving organizational climate, enhancing tutors’ extra role behavior, and designing more relevant education and training programs to support the long term sustainability of PKBM.